2016
DOI: 10.1007/s00595-016-1344-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implementing an “enhanced recovery after surgery” program on patients undergoing resection of hepatocellular carcinoma

Abstract: The ERAS program was feasible and effective for patients with chronic liver disease undergoing extended liver resection for HCC, because it allowed earlier oral dietary intake and promoted faster postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
0
19
1
1
Order By: Relevance
“…Six studies were RCTs, 22,25,28,29,32,35 16 were case-control studies 2, 18, 21, 23, 24, 27, 31, 33, 36-42 and five prospective studies. 19,20,26,30,34 Eleven studies included both open and laparoscopic surgery in the study, 19-21, 23, 24, 27, 33, 35, 37, 39, 40 ten studies included only open liver surgery patients, 2, 18, 25, 26, 30-32, 34, 41, 42 five studies included only laparoscopic surgery patients, 22,28,29,36,38 whilst one study performed a separate analysis for laparoscopic surgery and open surgery. 21 A detailed characteristic of included studies is shown in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Six studies were RCTs, 22,25,28,29,32,35 16 were case-control studies 2, 18, 21, 23, 24, 27, 31, 33, 36-42 and five prospective studies. 19,20,26,30,34 Eleven studies included both open and laparoscopic surgery in the study, 19-21, 23, 24, 27, 33, 35, 37, 39, 40 ten studies included only open liver surgery patients, 2, 18, 25, 26, 30-32, 34, 41, 42 five studies included only laparoscopic surgery patients, 22,28,29,36,38 whilst one study performed a separate analysis for laparoscopic surgery and open surgery. 21 A detailed characteristic of included studies is shown in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In addition, it is possible that hospitals with a shorter LOS, particularly within the more recent time period, have a higher proportion of patients undergoing laparoscopic liver resection and/or that those hospitals have adopted an enhanced recovery pathway for liver resection patients. Both laparoscopy and enhanced recovery have been associated with reduced complications and shorter LOS . It is unclear if these specific hospital traits are related to volume alone, other factors or a combination thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Both laparoscopy and enhanced recovery have been associated with reduced complications and shorter LOS. [31][32][33][34] It is unclear if these specific hospital traits are related to volume alone, other factors or a combination thereof.…”
mentioning
confidence: 99%
“…These findings show the importance of improving perioperative care to reduce morbidity rates among patients undergoing hepatectomy. ERAS protocols have been reported to be effective for patients undergoing hepatectomy since they lead to shorter hospitalization duration and reduced morbidity [6][7][8][9][10], although the quality and level of evidence for their efficacy are still lower than those for ERAS protocols for patients undergoing colorectal surgery. Therefore, we performed a randomized controlled trial (RCT) to determine whether an ERAS protocol is more effective compared to conventional postoperative management in patients undergoing open hepatectomy in our department.…”
Section: Introductionmentioning
confidence: 99%